DEVELOPMENT OF POLYMER BLEND MIXED MATRIX MEMBRANES FOR CO2/CH4 MIXTURE - FARNAM, MARJAN (2018)
Developing gas separation membranes with high performance is needed for efficient gas separation processes. Polymeric membranes are considered a promising candidate however these membranes show a trade-off behavior between their permeability and selectivity. The main objective of this research is to synthesize enhanced polymeric blend mixed matrix membranes (PB3Ms) consisting of polyethersulfone (PES), polyvinyl acetate (PVAc 5-20 wt. %) and carbon molecular sieve (CMS 5-20 wt. %) to improve carbon dioxide (CO2)/methane (CH4) separation performance.